Development and validation of bioanalytical liquid chromatography–tandem mass spectrometry method for the estimation of pentoxifylline in human plasma: Application for a comparative pharmacokinetic study. Issue 4 (August 2019) - Dodda, Sireesha; Makula, Ajitha; Polagani, Srinivasa R; Kandhagatla, Raj N
A method for bioanalysis of pentoxifylline in human plasma was developed using liquid chromatography–tandem mass spectrometry, which is simple, specific, and sensitive. Pentoxifylline D5 was used as the internal standard. Employing only 100 µl of human plasma, processing was done with solid-phase extraction technique. The analyte and the internal standard were separated from endogenous components on Ace phenyl column using a mixture of 5 mM ammonium acetate buffer and high performance liquid chromatography grade acetonitrile (60:40, v/v) as mobile phase at a flow rate of 1 ml/min. The linearity of the method was in the range of 3–1200 ng/ml with r 2  > 0.99. Positive ion MRM mode was used for the detection of the analyte and the internal standard. The method was validated as per the US Food and Drug Administration guidelines and the results were within the acceptance limits. The proposed method was applied for comparative pharmacokinetic study of pentoxifylline after oral administration of 400 and 600 mg tablets to South Indian male subjects under fed conditions.